(untitled) (Научни трудове на УНСС, 2023)
Construction and demolition industry is accountable for a large percentage of all the waste streams generated in Europe. Becoming a subject of international discussions and raising public awareness has led to increasing efforts to identify methods to achieve ‘green’ goals. This paper makes an overview of best practices and digital tools for the construction and demolition waste management in European counties which have proven themselves as leaders in the subject. The main challenges in front of Bulgaria to achieve a similar state are pointed out, together with the initial steps to be taken towards developing more optimized waste management processes.